2016
DOI: 10.21511/imfi.13(1).2016.06
|View full text |Cite
|
Sign up to set email alerts
|

Business efficiency of the commercial banks in ASEAN

Abstract: This study examines the determinants of cost inefficiency of banks operating in 8 member countries of the Association of Southeast Asian Nations (ASEAN): Indonesia, Malaysia, Singapore, Thailand, the Philippines, Cambodia, Brunei and Vietnam. The author defines the cost inefficiency using accounting based efficiency known as business efficiency (CIR). Second, the researcher regresses the cost inefficiency ration on a set of bank specific variables (size, equity to total asset, personnel expenses to total expen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
13
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 4 publications
3
13
1
1
Order By: Relevance
“…The findings indicate that credit risk has a negative impact on bank performance in both the long and short term. This is consistent with the findings of Muriithi et al (2016) and Amin et al (2014) regarding the negative impact of nonperforming loans on bank performance. However, the findings contradict those of Afriyie (2011) and Ogboi (2013), who found that credit risk positively influences bank performance.…”
Section: Roa Vif 1/vifsupporting
confidence: 92%
“…The findings indicate that credit risk has a negative impact on bank performance in both the long and short term. This is consistent with the findings of Muriithi et al (2016) and Amin et al (2014) regarding the negative impact of nonperforming loans on bank performance. However, the findings contradict those of Afriyie (2011) and Ogboi (2013), who found that credit risk positively influences bank performance.…”
Section: Roa Vif 1/vifsupporting
confidence: 92%
“…The first two factors affect efficiency negatively, whereas the last two variables affect it positively. The findings of this study are consistent with the findings of Berger et al (1993), Imtiaz et al (2019), Khandoker et al (2013) and Mongid (2016). The study contributes to the existing body of knowledge regarding efficiency determinants of non-bank financial services industry by identifying the firm-specific significant factors that affect NBFIs' efficiency from the context of Bangladesh.…”
Section: Conclusion and Recommendationssupporting
confidence: 90%
“…Firms may raise their production by 47.1% while utilizing identical input. Mongid (2016) investigated the factors of cost inefficiency in banks operating in eight ASEAN member nations. For the years 2008–2012, data from 504 institutions were utilized.…”
Section: Literature Review and Research Gapmentioning
confidence: 99%
“…Among all selected variables, size shows the highest standard deviation of 34.2. It is because the difference in the asset size among ASEAN banks is widespread (Mongid, 2016). Table 4 exhibits the correlation results.…”
Section: Results and Interpretationsmentioning
confidence: 99%